(untitled) (Sociologisk Forskning, 2017)
Sweden is often described as an environmental forerunner and one of the most ecologically modernized countries in the world, one where social welfare, economic growth and environmental protection mutually support each other. Examining the case of Swedish forestry, we discuss a number of tensions in this sector that mirror some general tensions in Swedish society and explore how these tensions can be understood as part of a transforming modernity.